2019
DOI: 10.1021/acs.macromol.9b01512
|View full text |Cite
|
Sign up to set email alerts
|

Intermingled Network of Syndiotactic Polystyrene/Poly(3-hexylthiophene)

Abstract: By taking advantage of the fiber forming properties of both polymers in p-xylene, syndiotactic polystyrene (sPS) and poly­(3-hexylthiophene) (P3HT) are mixed at an elevated temperature to prepare a composite network. These sPS–P3HT networks have been intensively investigated by UV–vis absorption, FTIR, and DSC; their morphologies by FE-SEM and FEG-TEM; and the molecular structure of the P3HT chains by neutron scattering experiments, rheology, and conductivity. Absorption measurements indicate the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A few spectral regions are of interest. In the P3HT spectrum, the peak at 1450 cm –1 is associated with the stretching vibration of the thiophene ring, and the peak at 1515 cm –1 is associated with the carbon–carbon double bond stretching vibration . The characteristic strong stretching vibrations of aliphatic (CH 2 ) bonds were also detected at 2906 cm –1 and 2851 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A few spectral regions are of interest. In the P3HT spectrum, the peak at 1450 cm –1 is associated with the stretching vibration of the thiophene ring, and the peak at 1515 cm –1 is associated with the carbon–carbon double bond stretching vibration . The characteristic strong stretching vibrations of aliphatic (CH 2 ) bonds were also detected at 2906 cm –1 and 2851 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 95%
“…The formation of organogels at a high P3HT concentration (∼10 mg mL –1 ) in various organic solvents has been reported. ,, The variation of the nanofibrillar network structure caused by the change in solvent quality has been shown to affect the conductivity values. Dried samples obtained from various organogels display conductivities as high as ∼10 –4 Scm –1 . ,,, In addition to the organogels with only P3HT, polymer gels consisting of polystyrene and P3HT have also been investigated. , In another study, the cogelation of poly­(γ-benzyl- l -glutamate) (PBLG) and P3HT has been reported, where it has been shown that both polymers interact to form interconnected networks . The in situ polymerization of conductive polymers in molecular gels has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of fibrils may be the wrapping of P3OT or insertion of P3OT chains onto/into 𝛿-form of sPS and indirectly supporting interactions of P3OT chains with the benzene group of the sPS chain (Figure 3). [15,22] Rheological tests to determine the storage modulus (G') and loss modulus (G'') have been performed to explore the viscoelastic properties of the pure sPS, and sPS-P3OT gel networks. In the frequency sweep, both moduli remain invariant over the frequency zone studied here and storage modulus is always greater than loss modulus, revealing viscoelastic nature of these networks.…”
Section: Resultsmentioning
confidence: 99%
“…As compared to sPS network, values of moduli in sPS-P3OT network have been significantly enhanced, indicating the intensive interaction between sPS and P3OT chains in the anisole medium (Table 2). [15,23]]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation